2003
DOI: 10.3121/cmr.1.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Cessation in Primary Care: Maximizing Intervention Strategies

Abstract: The most effective preventive intervention that a clinician can provide for tobacco-using patients against heart disease, cancer, cerebrovascular disease and chronic obstructive pulmonary disease is an empathic, personalized smoking cessation intervention program with extended assistance and follow-up. The goal of the intervention must be complete smoking cessation. Reduction provides no direct health benefits to the individual smoker. Interventions are readily available, but underutilized, in part due to lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 89 publications
1
47
0
7
Order By: Relevance
“…In fact, previous studies considered the inclusion of smokers 11,12,30,31 . The negative and nihilistic psychological profile of many of these patients 29 and its possible influence on adherence to the program and relapse of ex-smokers have been cited as possible deterrents to their inclusion in PR. Young et al 32 , for example, reported that current smoking was associated with non-adherence to the PR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, previous studies considered the inclusion of smokers 11,12,30,31 . The negative and nihilistic psychological profile of many of these patients 29 and its possible influence on adherence to the program and relapse of ex-smokers have been cited as possible deterrents to their inclusion in PR. Young et al 32 , for example, reported that current smoking was associated with non-adherence to the PR.…”
Section: Discussionmentioning
confidence: 99%
“…Although PR is considered useful for most patients in the moderate to advanced stages of the disease, the availability of such programs is limited, which stimulated the investigation of the most common limiting factors, especially current smoking. In this context, it should be recognized that smokers with lung or heart disease known to be associated with smoking and who continue to smoke have lower adherence to drug treatment than those who quit 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Bırakmayı düşünme aşamasında olanlardan %5'i relaps olmadan sürdür-me aşamasında kalırlar. Yeniden başlayanların %15'i düşünmeme, diğer %85'i düşünme ve hazırlık aşama-larına dönüş yapmaktadır (15) .…”
Section: Ruhsal Durumda Değişikliklerunclassified
“…Değişim aşamaları ile değişim yöntemleri arasında-ki ilişkiye bakıldığında, değişimin başlangıç dönem-lerinde daha çok bilişsel yöntemler kullanılırken, hazırlık, hareket ve devam ettirme gibi ilerleyen aşamalarında davranışsal yöntemlerin kullanıldığı görülmektedir (15). (17,18) .…”
Section: Sosyal öZgürleşmeunclassified
“…These intervention activities were summarized in a handbook that was presented to the CABs at the individual colleges. To ensure some commonalty of activities, an intervention manual was created that divided activities into four major categories: (a) increasing the awareness of the dangers of tobacco smoke (Backinger, Fagan, Matthews, & Grana, 2003), (b) increasing campus awareness and enforcement of restrictive tobacco control policies (Ding, 2005), (c) increasing awareness and availability of tobacco cessation resources (Abdullah, Lam, Chan, & Hedley, 2004;Anczak & Nogler, 2003;Mermelstein & Turner, 2006), and (d) increasing awareness of the special strategies employed by the tobacco industry to target special populations, such as minorities and students living in Greek housing (Hammond et al, 2005). As noted above, the intervention activities were selected based on previous studies that had shown effective cessation/prevention activities among adolescents and young adults.…”
Section: Interventionmentioning
confidence: 99%